ADVANCES IN RELIABILITY OPTIMIZATION OF MULTI-STATE SYSTEM - LI ChunYang; CHEN ShouHua; LI LingWei (Jixie qiangdu)
Multi-state system reliability is very important for complex systems which have a range of performance levels from perfect functioning to complete failure. The research works on reliability optimization of multi-state system promote the applications of multi-state system reliability. The paper provides a broad overview of recent research on reliability optimization of multi-state system,and discusses the further research directions. In particular,six issues are analyzed: redundancy allocation problem,maintenance / redundancy allocation problem,optimal allocation of elements,optimal reliability enhancement,multiobjective optimization,and optimization algorithms. The further research can be focused on fuzzy reliability optimization,reliability optimization in the presence of dependent failure,reliability optimization based on RAMS + C,and so on.